Downsizing : confronting our possessions in later life - Ekerdt, David J. (David Joseph), 1949- (Columbia University Press, 2020)
"Almost all older adults face a predicament in later life: their possessions. Ekerdt has estimated, based on national survey questions of my design, that 35 to 40 million persons aged 60+ hold the opinion that "I have more things than I need." The downsizing problem has spawned an entire industry of clutter manuals and elder-moving services. But for most older adults, divestment is not so simple. Ekerdt presents a unique, conceptual framing, casting the entirety of one's possessions as borne across time as a "convoy of material support." More than mere incidentals, possessions enact the life course and create our ideas about ourselves. For older adults, the material convoy is central to well-being. At the same time, this accumulated infrastructure is a potential obstacle to a more vital, independent way of life. Ekerdt's conclusions about the meaning and management of possessions are drawn from interviews with elders and family members in over 125 diverse U.S. households. In Downsizing he brings fresh observations about how the process goes, how people accomplish it, and the cognitive, physical, emotional, and social tasks that it entails"--